Keragaman fungi rhizosfer tanaman pisang kepok yang terinfeksi penyakit darah (Rastolnia syzygii subsp. celebesensis) di Bremi, Distrik Manokwari Utara, Papua Barat - Puspasari, Aninda; Mogea, Rina; M. R. Ruimassa, Reimas (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: Blood disease is a significant problem in Kepok banana cultivation, resulting in substantial economic losses. Blood disease is caused by the pathogenic bacteria Rastolnia syzygii subsp. celebecensis, a soil-borne disease. Soil microbes play a crucial role in the biocontrol process because they can produce certain enzymes or metabolites that can suppress disease-causing pathogens in plants. One approach is the use of fungi as antagonistic biological agents that can protect plants from disease attack. The presence of fungal biological agents in the rhizosphere of Kepok banana plants infected with blood disease requires isolation and identification of soil fungi to obtain data on the diversity of indigenous rhizosphere fungi in Kepok banana plants infected with blood disease in Bremi, North Manokwari District. The results of the isolation and identification of rhizosphere fungi in Kepok banana plants infected with blood disease yielded six (6) fungal isolates with high disease virulence and eleven (11) fungal isolates with moderate disease virulence. The fungal isolates obtained from the rhizosphere of high disease virulence were identified as Trichoderma sp1., Rhizoctonia sp., Aspergillus sp1., Aspergillus sp2., Trichoderma sp2., and Trichoderma sp3. Fungal isolates obtained from the rhizosphere of moderate disease virulence were identified as Fusarium sp1., Fusarium sp2., Penicillium sp1., Aspergillus sp1., Aspergillus sp2., Trichoderma sp1., Trichoderma sp2., Trichoderma sp3., Fusarium sp3., Penicillium sp2., and Penicillium sp3.